Optimal Risk Sharing and the Leasing of Natural Resources, with Application to Oil and Gas Leasing on the Ocs - Leland, Hayne E. (Quarterly Journal of Economics, 1978)
Journal Article Optimal Risk Sharing and the Leasing of Natural Resources, with Application to Oil and Gas Leasing on the OCS Get access Hayne E. Leland Hayne E. Leland University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 92, Issue 3, August 1978, Pages 413–437, https://doi.org/10.2307/1883152 Published: 01 August 1978